PERAN GURU DAN KEIKUTSERTAAN ORANG TUA DALAM MENANAMKAN NILAI AGAMA ISLAM PADA ANAK USIA 5-6 TAHUN - Sufa, Faila (BELIA: Early Childhood Education Papers, 2014)
Minimum 0-6 years of golden age at the same time is critical in the life cycle, which will determine the next child development, this period was the right time to put the foundations of the development of physical abilities, language, social-emotional, self-concept, morals, and values religion. The role of teachers and parents determine the childs subsequent behavior. The purpose of this study (1) To know how the teacherâs role and the participation of parents in instilling Islamic values in children 5-6 years old in early childhood in PAUD Sekar Nagari UNNES in a family environment, (2) To know the factors driving and inhibiting teachers in instilling religious values Islam in children aged 5-6 years in early childhood Nagari UNNES Sekar, (3) To know the factors of driving and inhibiting the parents in instilling Islamic values in children 5-6 years old in a family environment. The method of this research was qualitative descriptive approach is housed in PAUD Sekar Nagari UNNES. Sources of research data is teachers and parents also the documents that used as RKM and RKH. The methods of data collection are observation, interviews, and documentation. The result of the research showed that the teachers role in instilling Islamic values in early childhood education teaching Sekar Nagari about faith , morality , worship , and the qiroatul Qurâan was good . Meanwhile , the participation of parents in instilling Islamic values in the family environment on the education of worship , reading the Quran , good moral , and faith did well good . The driving factor in instilling Islamic values in early childhood Sekar Nagari is the motivation of parents and the childs motivation , while inhibiting factor is the lack of existing infrastructure and the level of activity of parents . The driving factor in instilling Islamic values in society is parental support , school support , and community support , while inhibiting factor is the family environment , school environment , and the environmental community.